2020
DOI: 10.4103/ijmr.ijmr_493_18
|View full text |Cite
|
Sign up to set email alerts
|

Genotype analysis of ofloxacin-resistant multidrug-resistant Mycobacterium tuberculosis isolates in a multicentered study from India

Abstract: Background & objectives: Drug resistance surveillance offers useful information on trends of drug resistance and the efficacy of control measures. Studies and reports of drug-resistant mutations and phenotypic assays thus become important. This study was conducted to investigate the molecular characteristics of ofloxacin (OFX)-resistant, multidrug-resistant tuberculosis (MDR-TB) isolates from different geographical regions of India and their association with strains of different genotypes. Further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…MDR-TB exhibits resistance to isoniazid and rifampicin, while XDR-TB exhibits resistance to all first-line drugs and at least one second-line drug [ 5 ]. Gupta et al reported that ofloxacin resistance is significantly high among multidrug-resistant MTB strains across India, most of which were especially associated with the Beijing genotype and carried gyrA mutations [ 6 ]. Fluoroquinolone is the classical representative of first-line drugs in TB treatment.…”
Section: Introductionmentioning
confidence: 99%
“…MDR-TB exhibits resistance to isoniazid and rifampicin, while XDR-TB exhibits resistance to all first-line drugs and at least one second-line drug [ 5 ]. Gupta et al reported that ofloxacin resistance is significantly high among multidrug-resistant MTB strains across India, most of which were especially associated with the Beijing genotype and carried gyrA mutations [ 6 ]. Fluoroquinolone is the classical representative of first-line drugs in TB treatment.…”
Section: Introductionmentioning
confidence: 99%